Exploring the Complexities of Sarcopenic Obesity and Nutritional Approaches for Promoting Healthy Aging: a Literature Review - Michelle Ruth Natalie; Alexander Halim Santoso (Universitas Malahayati Lampung, 2024)
ABSTRACT The ongoing global demographic transition towards an aging population indicates that the proportion of individuals aged 60 and above is expected to reach 21% by the year 2050, with more than 5% of this group being 80 or older. As a result of this shift in demographics towards an increasingly elderly population, there has been a noticeable increase in the occurrence of a medical condition known as sarcopenic obesity. This academic paper thoroughly examines the existing body of literature by consolidating information from various reputable sources. The primary focus of this review is to investigate the implementation of therapies related to obesity, sarcopenia, and nutrition. The data for this assessment was systematically collected by conducting an extensive search of electronic databases, encompassing research publications and review papers. It is crucial to acknowledge that traditional measures like body weight and body mass index are not advisable for assessing body composition in older adults because they cannot distinguish between adipose tissue and muscle mass. Sarcopenia is closely linked to inadequate dietary intake, while obesity results from excessive energy consumption, creating an imbalance between daily energy intake and expenditure. When formulating a nutritional strategy to address sarcopenic obesity, it is essential to consider dual goals. The primary goal is to ensure a proper intake of nutrients that promotes the growth of skeletal muscle mass or reduces the risk of muscle loss. At the same time, it is crucial to achieve balance by advocating for sufficient nutrition and energy intake to prevent the accumulation of excess fat tissue. Keywords: Sarcopenic Obesity, Elderly Population, Nutritional Therapeutic